2000
DOI: 10.1149/1.1393579
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction on Ru[sub 1.92]Mo[sub 0.08]SeO[sub 4], Ru/Carbon, and Pt/Carbon in Pure and Methanol-Containing Electrolytes

Abstract: The oxygen reduction reaction (ORR) activity of a Ru 1.92 Mo 0.08 SeO 4 catalyst, a Vulcan XC72-supported Ru catalyst and, for comparison, a Vulcan XC72-supported Pt catalyst was studied with a rotating ring-disk electrode. The very similar reaction characteristics of the two Ru catalysts in pure and CH 3 OH-containing H 2 SO 4 electrolyte, which differ markedly from those of the Pt catalyst, indicate that the reactive centers in both Ru catalysts must be identical. They are highly selective (>95%) toward redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
166
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 20 publications
(35 reference statements)
13
166
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Because of the sluggish ORR kinetics and the stability issues of the catalyst in the electrochemical environment, expensive precious metal catalysts are often used in these electrochemical devices to catalyze the ORR. 15 Conventionally, the performance of the catalyst is evaluated in an operating fuel cell mode using the DC methods.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Because of the sluggish ORR kinetics and the stability issues of the catalyst in the electrochemical environment, expensive precious metal catalysts are often used in these electrochemical devices to catalyze the ORR. 15 Conventionally, the performance of the catalyst is evaluated in an operating fuel cell mode using the DC methods.…”
mentioning
confidence: 99%
“…Non-noble metal catalysts based on chalcogenides [36][37][38][39] and macrocycles of transition metals [40][41][42][43][44] have shown good activity for the ORR. However these materials did not yet match the catalytic activity of dispersed platinum.…”
Section: Ii2 New Preparation Methods Of Efficient Electrode Catalystsmentioning
confidence: 99%
“…It was concluded that the Mo and Ru atoms, in Mo-Ru-Se, were located as independent phases: MoSex, MoOx and RuSex [76]. They, however, showed high selectivity to perform the ORR, in a solution containing methanol, with a four-electron reaction pathway, with an activity nevertheless, lower than that of the standard Pt catalysts in methanol-free electrolyte [77].…”
Section: Transition Metal Chalcogenidesmentioning
confidence: 97%